2009
DOI: 10.1364/ol.34.001462
|View full text |Cite
|
Sign up to set email alerts
|

High-energy ultrashort laser pulse compression in hollow planar waveguides

Abstract: International audienceWe demonstrate compression of high-energy ultrashort laser pulses by nonlinear propagation inside gas-filled planar hollow waveguides. We adjust the input beam size along the nonguided dimension of the planar waveguide to restrain the intensity below photoionization, while the relatively long range guided propagation yields significant self-phase modulation and spectral broadening. We compare the compression in different noble gases and obtain 13.6 fs duration with output pulse energy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Also, eliminating the onset of ionization becomes challenging as designs are scaled to higher pulse energies, although progress is being made with planar waveguides [6,7]. In filamentationbased schemes the complex filament structures generated at high intensities make exploring parameter spaces challenging both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Also, eliminating the onset of ionization becomes challenging as designs are scaled to higher pulse energies, although progress is being made with planar waveguides [6,7]. In filamentationbased schemes the complex filament structures generated at high intensities make exploring parameter spaces challenging both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…In the first experimental realization it was recognized that modulational instability due to one-dimensional, small-scale selffocusing along the unguided waveguide direction could result in strong deterioration of the transverse beam profile and in the extreme to break-up of the beam into several filaments [20]. Shortly after, some of the authors of this publication showed that by carefully controlling experimental parameters, such as gas pressure and waveguide length, a balance between spectral broadening and beam deterioration can be achieved and demonstrated compressed pulses at the 10 mJ level with good focusability [21,22]. Furthermore, a theoretical model describing a stability regime for energy up-scaling of the planar hollow waveguide compression scheme was introduced [23].…”
Section: Introductionmentioning
confidence: 94%
“…52 Because the input laser beam is confined only in the lateral direction perpendicular to the waveguide plane, thus enlarging the mode area, few cycle pulses with much higher energies can be generated. [8][9][10] In the former scheme spatial beam quality still remains a problem. A summary of the most important laser sources delivering intense few-cycle pulses in the NIR is listed in table 2.1.…”
Section: Filamentationmentioning
confidence: 99%
“…In other words, in a frame of reference moving at the velocity SF , the delayed pump pulses with the group velocities 1 and 2 will travel towards 9 12 fs / 2 mJ Chirped mirrors Akturk et al (2009) 8 11.5 fs / 7.6 mJ Chirped mirrors Chen et al (2011) 10 9.4 fs / 9.1 mJ Chirped mirrors each other (see Fig. 2.5).…”
Section: Nonlinear Pulse Compressionmentioning
confidence: 99%
See 1 more Smart Citation